Evaluación de la producción de biogás en un reactor metanogénico escalonado (RME) usando cenizas de cascarilla de arroz como material adsorbente para diferentes cargas orgánicas (OLR) (2020)
The present work aimed to evaluate the production of Biogas from synthetic wastewater at a concentration of 2000mg / L of COD, performing its degradation through anaerobic digestion in a single stage, using two prototype anaerobic bioreactor diameters 4.12L variable in addition to checking the influence of rice husk ash as an adsorbent material in the performance of anaerobic digestion. This idea stems from the use of residues with lignocellulosic organic matter, which are the most abundant in agro-industrial processes, thus generating new sources of energy, through the biochemical transformation of organic matter through the digestion process. anaerobic, contributing to the GRESIA research group of the Antonio Nariño University.